2016
DOI: 10.1158/1055-9965.epi-16-0104
|View full text |Cite
|
Sign up to set email alerts
|

Selenium- or Vitamin E–Related Gene Variants, Interaction with Supplementation, and Risk of High-Grade Prostate Cancer in SELECT

Abstract: Background Epidemiological studies and secondary analyses of randomized trials supported the hypothesis that selenium and vitamin E lower prostate cancer risk. However, the Selenium and Vitamin E Cancer Prevention Trial (SELECT) showed no benefit of either supplement. Genetic variants involved in selenium or vitamin E metabolism or transport may underlie the complex associations of selenium and vitamin E. Methods We undertook a case-cohort study of SELECT participants randomized to placebo, selenium or vitam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 58 publications
(46 reference statements)
3
35
0
2
Order By: Relevance
“…75,76,79,80 Genetic SNP's that resulted in an increase of serum α-T levels were shown to be associated with a decrease in cancer risk. 43,44 All these results support the concept that insufficiency in VE nutrition increases cancer risk.…”
Section: Assessment Of Human Studies and Mechanistic Considerationssupporting
confidence: 73%
See 2 more Smart Citations
“…75,76,79,80 Genetic SNP's that resulted in an increase of serum α-T levels were shown to be associated with a decrease in cancer risk. 43,44 All these results support the concept that insufficiency in VE nutrition increases cancer risk.…”
Section: Assessment Of Human Studies and Mechanistic Considerationssupporting
confidence: 73%
“…43 More recently, three additional SNP variations (involving SEC14L2, we SOD1, and TTPA) were found to be associated with a lower risk of prostate cancer in subjects receiving VE in the SELECT. 44 The SNP variation for both SEC14L2 and SOD1 were associated with significantly lowered prostate cancer risk. The SNP of TTPA, which results in lower levels of α-TTP and presumably lower α-T, was associated with increased risk of prostate cancer in the absence of VE supplementation, and VE supplementation seemed to offset this increased risk.…”
Section: Prostate Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…In cancer, the SNP rs699473 is associated with increased risk of high-grade prostate cancer [211]. Interestingly, this SNP was also found to protect patients from increased risk of high grade prostate cancer after selenium supplementation in the Selenium and Vitamin E Cancer Prevention Trial (SELECT) [212]. In breast cancer, SNP rs699473 is associated with a significant reduction in the progression-free survival in breast cancer compared to patients with wild type EcSOD [118].…”
Section: Deregulation Of Ecsod In Cancersmentioning
confidence: 99%
“…However, its use has been associated with weight gain [31] , and there are concerns regarding increased risk of heart failure [32] , bladder cancer [33] , and osteoporosis [34] . Similarly vitamin E, a widely investigated antioxidant, has been shown to improve steatosis and inflammation in several RCTs in both diabetic and non-diabetic children and adults [35] , but one study suggested an increased risk of prostate cancer [36] , and another an increased risk of haemorrhagic stroke [37] . Risks and benefits of using such agents must therefore be carefully considered and discussed with each patient in detail before they can be recommended.…”
Section: Early Adoption Of New Diagnostics and Treatments Transient Ementioning
confidence: 99%